Pelatihan Bahasa dan Budaya Jepang sebagai Sarana Pengenalan Bahasa Asing Bagi Siswa SMP Islam Al Maarif 02 Singosari - Dewandono, Wiranto Aji; Sutiyarti, Ulfah; Saragih, Febi Ariani (Faculty of Cultural Studies, Universitas Brawijaya, 2023)
This Community Service program aims to introduce the language and culture of Japanese society to students at SMP Islam Al Maarif 02 Singosari. Foreign language education has not been widely implemented in junior high schools. In formal education, foreign languages such as Arabic, Japanese, Mandarin, and German are introduced at the junior high school level in the early semesters through a system where students choose based on their interests. This is what prompted the Community Service team from the Japanese Language Education Program to engage directly with middle school students, with the goal of introducing them to the language and culture of Japanese society. This way, when the students targeted by this Community Service initiative enter the secondary education level, they will already be familiar with the Japanese language and culture, and it is hoped that they will choose Japanese as one of their foreign language subjects to study. In other words, this Community Service program serves as a promotional platform for the Japanese Language Education Program under the Department of Language Education at FIB UB. The Community Service activity was conducted on August 5, 2022, at the meeting room of SMP Islam Al Maarif 02 Singosari. The forms of this Community Service activity were: 1) Introducing basic Japanese language, 2) Making Japanese cuisine such as Sushi and Onigiri, and introducing the daily life of schoolchildren in Japan.